2010
DOI: 10.1103/physrevb.81.165114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electron correlations on structural phase stability, magnetism, and spin-dependent transport inCeMnNi4

Abstract: First-principles calculations are carried out to study the effect of electron correlations on relative structural stability, magnetism, and spin-dependent transport in CeMnNi 4 intermetallic compound. The correct description of Coulomb repulsion of Mn 3d electrons is shown to play a crucial role in reproducing the experimentally observed cubic phase of CeMnNi 4 as well as its relatively high degree of transport spin polarization ͑ϳ66%͒. These are the two fundamental properties of this compound which convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
(27 reference statements)
2
9
0
Order By: Relevance
“…has not been independently deduced, such as from structural or compressibility features of the compound, our results suggest that the U, if present, may be much smaller. Our work and the work of Bahramy et al23 ͑Color online͒ Total and site projected DOS of CeMnNi 4 for ordered ͑fcc͒ structure.…”
supporting
confidence: 50%
See 4 more Smart Citations
“…has not been independently deduced, such as from structural or compressibility features of the compound, our results suggest that the U, if present, may be much smaller. Our work and the work of Bahramy et al23 ͑Color online͒ Total and site projected DOS of CeMnNi 4 for ordered ͑fcc͒ structure.…”
supporting
confidence: 50%
“…23. Bahramy et al 23 showed that tuning to the value of U ϳ 6 eV one can get spin polarization very close to the experimental ͑Andreev͒ value. Our results show that using the experimentally observed abundance of antisite disorder, we obtain a spin polarization ϳ47% without invoking U.…”
Section: B Theoretical Calculationsmentioning
confidence: 63%
See 3 more Smart Citations